Impact of Multiplex PCR on Diagnosis of Bacterial and Fungal Infections and Choice of Appropriate Antimicrobial Therapy - Francesca Serapide; Rita Pallone; Angela Quirino; Nadia Marascio; Giorgio Settimo Barreca; Chiara Davoli; Rosaria Lionello; Giovanni Matera; Alessandro Russo (Diagnostics)
Multiplex Polymerase Chain Reaction (PCR) has significantly impacted the field of infectious disease diagnostics, offering rapid and precise identification of bacterial and fungal pathogens. Unlike traditional culture methods, which may take days to yield results, multiplex PCR provides diagnostic insights within hours, enabling faster, targeted antimicrobial therapy and reducing the delay in treating critical infections like sepsis. The technique’s high sensitivity and broad pathogen coverage make it ideal for both single and polymicrobial infections, improving outcomes across respiratory, bloodstream, and bacterial/fungal infections. However, multiplex PCR is not without challenges; initial high costs and the need for specialized training can limit its adoption, especially in low-resource settings. This review discusses the clinical advantages and limitations of multiplex PCR, highlighting its influence on diagnostic accuracy, antimicrobial stewardship, and the global fight against antimicrobial resistance (AMR). Furthermore, recent innovations in multiplex PCR, such as digital PCR and portable devices, are explored as potential tools for expanding access to rapid diagnostics worldwide.